Interviews avec Soudré Robert (Globalization and health policy in West Africa, 2022)
Interviews conducted with health institutions, health district managers, associations and NGOs working in the field of health on the issue of global health and the interactions between the actors in charge of health in Burkina Faso.
Keywords: World health; Health; Gender; West Africa; Global Health; Men who have Sex with Men; The Global Fund to Fight AIDS, Tuberculosis and Malaria; Joint United Nations Programme on HIV/AIDS; Global Health Policy; Burkina Faso